A Triple Band Substrate Integrated Waveguide with Dielectric Resonator Antenna for 4G and 5G Applications - Irene Kong Cheh Lin; Mohd Haizal Jamaluddin; Abinash Gaya (Micromachines, 2023)
A triple-band substrate integrated waveguide (SIW) with dielectric resonator antenna (DRA) for fourth-generation (4G) and fifth-generation (5G) applications is proposed and analyzed in this paper. Loading SIW with DRA allows for a wide bandwidth, low losses, and fabrication ease. The proposed antenna can transmit and receive data independently by covering LTE Band 3 at 1.8 GHz, LTE Band 8 at 2.6 GHz, and 5G n77 at 3.7 GHz. A U-shaped cut is applied to achieve the targeted multi-resonance frequencies. The antenna obtains high bandwidths of up to 19.50% with 4.9 dBi gain and 81.0% efficiency at 1.8 GHz, 6.58% bandwidth with 4.4 dBi and 72.7% efficiency at 2.6 GHz, and 8.21% bandwidth with 6.7 dBi and 73.5% efficiency at 3.7 GHz. The simulated and measured results agree well. The proposed antenna is feasible for 4G and 5G applications.